Infection by HPV in the oral cavity - A literature review - Augé, Luciana Barros; Bier, Bruno Martinazzo; Carpilovsky, Paula Köhler; Carpilovsky, Cristiane Köhler; Krause, Luciana Maria Fontanari (Disciplinarum Scientia | Saúde, 2021)
Human papillomavirus (HPV) is a microorganism that has the potential to infect the skin and mucous membranes, causing local tissue injury or remaining asymptomatic. When one’s immune system is not capable of fighting an invasion of the virus, it remains latent inside the nucleus of infected cells. One of the clinical manifestations is the presence of benign epithelial lesions in the oral cavity, which include squamous cell papilloma, common skin warts, focal epithelial hyperplasia and papillary hyperplasia. Human papillomaviruses have an etiological role in cancers of the pharynx and the oral cavity, with 25-50% of cases being attributed to HPV infections. A literature review was carried out in big contemporary databases and included papers from any year of publishing, going back as far as reviewing the history of its viral taxonomic classification all the way to current clinical approaches and therapies to patients with this infection, as well as immunization strategies with vaccines. It has been observed that the development of oropharyngeal cancer in a younger and non-smoking population could be attributable to HPV as an independent causal factor and has been a subject of increasing interest for the research community. HPV vaccination is expected to impact oral HPV incidence rates, leastwise for the genotypes included in the vaccine.